Rotating Neutron Stars with Relativistic Ab Initio Calculations - Xiaoying Qu; Sibo Wang; Hui Tong (The Astrophysical Journal, 2025)
The equation of state (EOS) of extremely dense matter is crucial for understanding the properties of rotating neutron stars. Starting from the widely used realistic Bonn potentials rooted in a relativistic framework, we derive EOSs by performing state-of-the-art relativistic Brueckner–Hartree–Fock calculations in the full Dirac space. The self-consistent and simultaneous consideration of both positive- and negative-energy states (NESs) of the Dirac equation allows us to avoid the uncertainties present in calculations where NESs are treated using approximations. To manifest the impact of rotational dynamics, several structural properties of neutron stars across a wide range of rotation frequencies and up to the Keplerian limit are obtained, including the gravitational and baryonic masses, the polar and equatorial radii, and the moments of inertia. Our theoretical predictions align well with the latest astrophysical constraints from observations of massive neutron stars and joint mass–radius measurements. The maximum mass for rotating configurations can reach up to 2.93 M _⊙ for Bonn A potential, while the radius of a 1.4 M _⊙ neutron star in the nonrotating case can be extended to around 17 km through constant baryonic mass sequences. Relations with good universalities between the Keplerian frequency and static mass as well as radius are obtained, from which the radius of the black widow PSR J0952-0607 is predicted to be less than 19.58 km. Furthermore, to understand how rotation deforms the equilibrium shape of a neutron star, the eccentricity is also calculated. The approximate universality between the eccentricity at the Keplerian frequency and the gravitational mass is found.